Happy to Welcome Menarche: Effectiveness of Educational Comic Media in Reducing Menstrual Anxiety among Pra-Adolescent Girls - Azwaldi; Agustin, Ismar; Putri, Prahardian; Muliyadi (International Journal Scientific and Professional, 2025)
Menarche, or a girl’s first menstrual period, is a significant milestone in adolescent development. However, for many young girls, this event is accompanied by anxiety, fear, and confusion due to a lack of appropriate education and open discussion. This study evaluates the effectiveness of the educational comic book "Happy to Welcome Menarche" as a media tool to reduce anxiety and improve understanding of menstruation among girls aged 9–12. The research utilized a pre-posttest design with a sample of elementary school students. Results showed a significant decrease in anxiety levels after reading the comic, with average scores dropping from 3.8 to 2.4 on a 5-point Likert scale (p-value = 0.001). The comic was praised for its engaging visuals, simple language, and relatable narrative, which together made complex topics easier to understand. In addition to its educational impact, a structured marketing strategy using social media, school collaborations, and health institutions was found to be effective in reaching the target audience. This study demonstrates that educational comics are a powerful, child-friendly medium for delivering reproductive health education and reducing psychological distress related to menarche.